Linked administrative data: providing unique solutions to key challenges in developmental and life-course criminology - Thompson, Carleen (Frontiers in developmental and life-course criminology, 2024)
To advance developmental and life-course criminology (DLC), field leaders have called for more: (a) replication and differentiation studies; (b) consideration of the impact of historical context and jurisdictional system changes; and (c) examination of within-individual change. These are largely appeals for adherence to fundamental scientific principles and the consideration of foundational life-course concepts, yet they remain key challenges for the field. We argue that linked administrative datasets provide unique solutions to these challenges and can support traditional longitudinal cohort survey designs to propel the DLC field forward. In this chapter we detail these three challenges facing the DLC field and the limitations to addressing these challenges using traditional longitudinal cohort surveys. We provide an overview of the core features and advantages of linked administrative datasets for addressing these challenges. We describe how linked administrative data facilitate methodological and theoretical innovation and can assist in bridging the gap between research, policy, and practice. We conclude with a discussion of limitations associated with these data, and recommendations for the appropriate use of this powerful methodology in future DLC research.